Mathematical modeling of the hematocrit influence on cerebral blood flow in preterm infants. - Irina Sidorenko; Varvara Turova; Esther Rieger-Fackeldey; Ursula Felderhoff-Müser; Andrey Kovtanyuk; Silke Brodkorb; Renée Lampe (PLoS ONE, 2021)
Premature birth is one of the most important factors increasing the risk for brain damage in newborns. Development of an intraventricular hemorrhage in the immature brain is often triggered by fluctuations of cerebral blood flow (CBF). Therefore, monitoring of CBF becomes an important task in clinical care of preterm infants. Mathematical modeling of CBF can be a complementary tool in addition to diagnostic tools in clinical practice and research. The purpose of the present study is an enhancement of the previously developed mathematical model for CBF by a detailed description of apparent blood viscosity and vessel resistance, accounting for inhomogeneous hematocrit distribution in multiscale blood vessel architectures. The enhanced model is applied to our medical database retrospectively collected from the 254 preterm infants with a gestational age of 23-30 weeks. It is shown that by including clinically measured hematocrit in the mathematical model, apparent blood viscosity, vessel resistance, and hence the CBF are strongly affected. Thus, a statistically significant decrease in hematocrit values observed in the group of preterm infants with intraventricular hemorrhage resulted in a statistically significant increase in calculated CBF values.